SERVICE QUALITY AND OPERATIONAL PERFORMANCE OF HOTELS IN PORT HARCOURT, NIGERIA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2019)
This study investigated the nexus between service quality and operational performance of hotels in Port Harcourt.Service quality was dimensioned by tangibiles, assurance, responsiveness,reliability and empathy; while operational performance was measured by customer satisfaction. Cross-sectional survey design was adopted for the study. The target population comprised both the managers and customers of hotels in Port Harcourt with a sample size of 120 respondents drawn for the study. The findings indicated that service quality dimensions correlated strongly with customer satisfaction. Based on this, it was concluded that service quality dimensions are good predictors of the operational performance of Port Harcourt Hotels. The study recommended that operators of hotels in Port Harcourt should be intentional in the quality of service they render since it is capable of affecting the level of satisfaction among their customers,train their service employees on service quality delivery and pay particularattention to the emphaty dimension.